Архівні документи про історію Поліської історико-технологічної експедиції 30-х років ХХ ст. - Станиціна, Г.О.; Виногродська, Л.І. (Археологія і давня історія України, 2017)
Стаття вводить до наукового обігу невідомі архівні матеріали, що стосуються історії Поліської
експедиції й зберігаються в Науковому архіві Інституту археології НАН України. Статья вводит в научный оборот малоизвестные
документы, хранящиеся в фондах Научного архива
Института археологии НАН Украины, и касающихся истории и деятельности Полесской историко-технологической экспедиции 1930—1933 гг. Is the article there is an overview of the documents
from the Scientific Archive of the institute of the Archaeology
of Ukraine concerning Polish Expedition
1930—1933. The data shows that in connection with
the industrialization of the country the peat was regarded
as local fuel for 1930—1934 years. During the extraction of peat a lot of archaeological
finds were revealed: tools, ornaments, remains of buildings on stilts, bridges, roads in the swamps, boats
etc. This fact drew attention of archeologists who put a lot of effort into preserving these finds.